Level of Salivary Uric Acid in Gingivitis and Periodontitis Patients - Muhammad Ihsan Rizal; Stiefani Vega (Faculty of Dentistry, Universitas Trisakti, 2017)
Background: Periodontal disease is common chronic adult condition. Antioxidants are present in the body fluid as protection against free radical. Uric acid is one of antioxidants that can be found in saliva. Moreover, the relationship among the antioxidant enzymes activities and clinical periodontal status were investigated. Objectives: The aim of the study was to observe uric acid level activities in the saliva of gingivitis and periodontitis patients. Methods: Six patients with gingivitis and six patients with periodontitis in Dental Hospital Trisakti University were included in the study. Clinical condition of each subject, the plaque index, and probing depth were determined. The salivary uric acid level was measured using the Folin-Wu method. Result: Salivary uric acid levels in the periodontitis patients with a mean ± SD 7.40 ± 0.31 (p = 0.004) were found to be higher compared to the gingivitis patients (mean ± SD = 6.84 ± 0.19). In addition, there were no significant differences in salivary uric acid levels between gender (p = 0.641). Conclusion: Uric acid levels in periodontitis patients were found to be higher than in gingivitis patients. Moreover, uric acid has more role on periodontitis than in gingivitis as an antioxidant agent.